(untitled) (Research, Society and Development, 2023)
Aging is a worldwide phenomenon and a phase of life that every individual will go through one day. This physical change caused by aging can lead to balance deficits and gait disorders, leading to falls and functional limitations, which can have consequences for the health of the elderly, such as fractures, skin injuries, reduced mobility and difficulty in performing tasks. Activities of Daily Living -.AVD. Kinesiotherapy prevents and treats intercurrent functional kinetic disorders in organs and systems of the human body, generated by genetic changes, trauma and acquired diseases and anticipating such situations is important since with preventive actions it is possible to prevent the occurrence of accidents. This article aims to contribute to the preservation of functional motor function, aiming to achieve autonomy and most importantly, improve quality of life. The search for studies was carried out in electronic databases: Google Scholar, SciELO, Lilacs – Bireme. The inclusion criteria were: Articles available in full, in Portuguese from 2018 to 2023, with free access and that had an affinity with the theme. A total of 40 publications were identified, after applying the inclusion criteria, 20 studies remained. We conclude that physiotherapists are crucial with their technical and scientific knowledge, using kinesiotherapy promoting improvements for healthy aging and encouraging people to pay more attention to the health of the elderly.